PATHET SEBAGAI STRUKTUR ADEGAN WAYANG KULIT JAWATIMURAN SUBGAYA MALANGAN - Pangestu, Dwi Cahyo; Suhita, Raheni; Suryanto, Edy (PANGGUNG, 2023)
Malangan’s puppet is a shadow puppet that grows and develops in East Jawa, precisely in the Greater Malang area. Malangan’s puppet differs from other styles in the scene structure department, which is covered by five pathet (Javanese gamelan modes) concepts. The purpose of this research is to describe the structure of the scene using five pathet concepts with the sample of the Malangan’s puppet script, Gathotkaca Lair. This Study applied the descriptive qualitative method. The research data were drawn from the data source of the Malangan’s puppet script with the Gathotkaca Lair’s play. The data collection employed content analysis techniques by evaluating several character dialogues that represent the scene structure in each pathet. The data analysis technique implemented the Miles & Huberman interactive model. The results of the study suggest that the scene structure in the Gathotkaca Lair’s script is well packaged into five pathets. The five pathets are pathet sepuluh (tenth), pathet wolu (eight), pathet sanga (ninth), pathet miring, and pathet serang. Pathet sepuluh serves as the opening act, while pathet serang is the closing act. Keywords: Structur of the Scene,, Malangan’s Puppet, Pathet